Successful deceased donor kidney transplantation to a recipient with a history of COVID-19 treatment. Issue 7 (July 2021) - Yoshinaga, Kasumi; Araki, Motoo; Wada, Koichiro; Hasegawa, Kou; Sekito, Takanori; Miyake, Shuji; Watari, Shogo; Maruyama, Yuki; Sadahira, Takuya; Nishimura, Shingo; Tanabe, Katsuyuki; Takeuchi, Hidemi; et al.
Abstract: Case presentation. A 49-year-old Asian male, who had undergone hemodialysis for >16 years, complained of a fever, dysgeusia and dysosmia, and was diagnosed with COVID-19 pneumonia based on severe acute respiratory syndrome coronavirus 2 polymerase chain reaction (SARS-CoV-2 PCR) and computed tomography (CT). Treatment was started with oral favipiravir and ciclesonide inhalation. On the 10th day of treatment, the patient had a persistent high fever and a chest CT showed exacerbation of pneumonia, so dexamethasone was intravenously started. He was discharged after confirming two consecutive negative SARS-CoV-2 PCR tests. Three months after COVID-19 treatment, a SARS-CoV-2 PCR test was negative and he underwent a deceased donor kidney transplantation. Basiliximab induction with triple drug immunosuppression consisting of extended-release tacrolimus, mycophenolate mofetil and prednisolone, which is our regular immunosuppression protocol, was used. He was discharged on postoperative day 18 without the need for postoperative hemodialysis or any complications. The serum creatinine level was 1.72 mg/dL 95 days postoperatively and he had a favorable clinical course that was similar to deceased donor kidney recipients without a history of SARS-CoV-2 infection. Conclusion. We report the first case of a kidney transplantation after COVID-19 treatment in Japan and the fourth case globally. We would like to provide information about our successful case due to the anticipated increase in similar candidates in the near future.